Mechanisms of reduced peak oxygen consumption in subjects with uncomplicated type 2 diabetes - Nesti, Lorenzo; Pugliese, Nicola Riccardo; Sciuto, Paolo; De Biase, Nicolò; Mazzola, Matteo; Fabiani, Iacopo; Trico, Domenico; Masi, Stefano; Natali, Andrea (Cardiovascular diabetology, 2021)
Type 2 diabetes mellitus (T2D) increases the risk of incident heart failure (HF), whose earliest fingerprint is effort intolerance (i.e. impaired peak oxygen consumption, or VO ). In the uncomplicated T2D population, however, the prevalence of effort intolerance and the underpinning mechanistic bases are uncertain. Leveraging the multiparametric characterization allowed by imaging-cardiopulmonary exercise testing (iCPET), the aim of this study is to quantify effort intolerance in T2D and to dissect the associated cardiopulmonary alterations. Eighty-eight adults with well-controlled and uncomplicated T2D and no criteria for HF underwent a maximal iCPET with speckle tracking echocardiography, vascular and endothelial function assessment, as well as a comprehensive biohumoral characterization. Effort intolerance was defined by a VO below 80% of maximal predicted oxygen uptake. Forty-eight patients (55%) had effort intolerance reaching a lower VO than T2D controls (16.5 ± 3.2 mL/min/kg, vs 21.7 ± 5.4 mL/min/kg, p < 0.0001). Despite a comparable cardiac output, patients with effort intolerance showed reduced peak peripheral oxygen extraction (11.3 ± 3.1 vs 12.7 ± 3.3 mL/dL, p = 0.002), lower VO /work slope (9.9 ± 1.2 vs 11.2 ± 1.4, p < 0.0001), impaired left ventricle systolic reserve (peak S' 13.5 ± 2.8 vs 15.2 ± 3.0, p = 0.009) and global longitudinal strain (peak-rest ΔGLS 1.7 ± 1.5 vs 2.5 ± 1.8, p = 0.03) than subjects with VO above 80%. Diastolic function, vascular resistance, endothelial function, biohumoral exams, right heart and pulmonary function indices did not differ between the two groups. Effort intolerance and reduced VO is a severe and highly prevalent condition in uncomplicated, otherwise asymptomatic T2D. It results from a major defect in skeletal muscle oxygen extraction coupled with a subtle myocardial systolic dysfunction.